Außerordentlicher SPD-Parteitag 1972 in Dortmund; 12.10.1972 - 13.10.1972 (2010)
2. Verhandlungstag am 13. Oktober 1972:<NZ>Schlußwort Willy Brandt:<NZ>Willy Brandt, Protokoll Seiten 123 - 133, 00'01'' - 39'50'';<NZ>Klaus Schütz, Protokoll Seite 134, 41'00'' - 41'34''.;